2022
DOI: 10.7554/elife.69255
|View full text |Cite
|
Sign up to set email alerts
|

The oncoprotein BCL6 enables solid tumor cells to evade genotoxic stress

Abstract: Genotoxic agents remain the mainstay of cancer treatment. Unfortunately, the clinical benefits are often countered by a rapid tumor adaptive response. Here, we report that the oncoprotein B cell lymphoma 6 (BCL6) is a core component that confers solid tumor adaptive resistance to genotoxic stress. Multiple genotoxic agents promoted BCL6 transactivation, which was positively correlated with a weakened therapeutic efficacy and a worse clinical outcome. Mechanistically, we discovered that treatment with the genot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…BCL6 was reported to act as proto-oncogene by affecting cancer hallmark pathways including proliferation, DNA repair, anti-apoptosis, and enable cancer cells to adapt to stress 25 . As a highly conserved protein, BCL6 play nonredundant role in immune modulation.…”
Section: Discussionmentioning
confidence: 99%
“…BCL6 was reported to act as proto-oncogene by affecting cancer hallmark pathways including proliferation, DNA repair, anti-apoptosis, and enable cancer cells to adapt to stress 25 . As a highly conserved protein, BCL6 play nonredundant role in immune modulation.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed the higher expression of biomarkers associated with radioresistance in pretreatment specimens of the TME of patients with recurrent anal cancer. Specifically, higher phospho-Akt expression (associated with PI3K/mTOR signaling activation and radioresistance) [ 35 , 36 , 37 ], higher BCL-6 (associated with anti-apoptotic activity in response to DNA damage-induced stress) [ 38 , 39 ] and higher phospho-GSKβ (associated with the activation of oncogenic Wnt/β-catenin, MAPK, PI3K/mTOR and Notch signaling activity) [ 40 , 41 ] were measured at higher levels in this cohort relative to their counterparts who were eventually cured by chemoradiation. Based on these findings, it is possible that tumors in the prognostically unfavorable anal cancer group who recurred were predisposed to overcome induced stress on the DNA by both cytotoxic chemotherapy and radiotherapy in order to account for the inability to achieve a curative outcome by multimodality treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combined inhibition of BCL6 and STAT3 synergistically defeats intratumoral heterogeneity in a subset of non–small cell lung cancers ( 20 ). We recently revealed that BCL6 enables solid tumor cells to evade genotoxic stress ( 21 ), and pharmacological inhibition of BCL6 enhances the sensitivity of KRAS -mutant lung cancer cells to clinical BETi ( 22 ). However, the biological function of BCL6 in KRAS -mutant lung tumorigenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%